Challenges and Opportunities for SMEs in Supply Chain Digital Transformation - Foroughi, Abbas (Archives of Business Research, 2025)
Digital transformation of supply chains has been successfully achieved by larger companies, but small-to-medium enterprises (SMEs) have shown much less progress. This study examined the state of digital transformation in a region with a significant number of SMEs, the ongoing challenges and opportunities these companies face, and the degree of support for potential training offered by a business school. A survey was developed to determine challenges related to supply chain operations, digital technologies in use, plans for future innovations, current employee skill levels, and support for employee training by a local business school. The survey revealed cybersecurity risk, demand forecasting, hiring/retaining talent, and customer behavior/expectations as supply chain challenges. Cloud computing and supply chain network optimization were the only technologies widely used. Digital skills were lacking and planning for digital limited, but there was overwhelming support for employee training. SME-particular issues and experiences related to progress toward digital transformation have not been widely researched. This study addressed these issues and provided insights that are useful for SMEs in the regional economy, as well as for SMEs around the world who seek digital transformation. Results underscored the importance of employee training in digital transformation and the need for a proactive supportive role by third-party entities such as higher education institutions. SMEs, which are 99% of all enterprises, are for the most part not participating in digital business. This issue has serious consequences for business communities around the world, who are missing out on opportunities to grow, expand, and remain competitive.